Performance of agronomical and seed biochemical traits of soybean genotypes in relation to their tolerance and preference by Nezara viridula - HERU KUSWANTORO; ERLIANA GINTING; JOKO SUSILO UTOMO; ERIYANTO YUSNAWAN (Biodiversitas Journal of Biological Diversity, 2019)
Kuswantoro H, Ginting E, Utomo JS, Yusnawan E. 2019. Performance of agronomical and seed biochemical traits of soybean genotypes in relation to their tolerance to and preference by Nezara viridula. Biodiversitas 20: 356-363. Qualitative and quantitative variations of biochemical compounds in plant organs is one of the causes leading to infestation by a certain pest which prefers to feed on particular genotypes than other genotypes. Objectives of this study is to find out the relationship of selected agronomical features and seed biochemical contents of soybean genotypes with their tolerance to Nezara viridula and also the preference of N. viridula to these genotypes. A total of 50 soybean germplasm were grown at Muneng research station during the dry season of 2016. The variability of the tested germplasm was reflected in the diversity of agronomic characters and seed biochemical contents. There was a significant positive correlation among the studied seed biochemical parameters, namely protein, methionine and cysteine contents. The protein and cysteine contents did not relate to N. viridula preference, but it was related to soybean tolerance against N. viridula. It was indicated by the insignificant positive correlation of protein and cysteine contents with the number of unfilled pods and the negative correlation of protein and cysteine contents with the ratio of number of unfilled pods to the total number of pods. Methionine content increased N. viridula preference, but it had no effect on soybean tolerance. Five genotypes, namely MLGG 0164, MLGG 0195, MLGG 0103, MLGG 0896 and MLGG 0196 were selected based on high seed biochemical contents which can be used as gene sources in soybean breeding programs. Among these five genotypes, MLGG 0195 had high protein, methionine and cysteine contents, but it was not tolerant to N. viridula. Hence, this genotype should be cultivated by controlling N. viridula optimally. MLGG 0196 had the highest methionine content, relatively high cysteine content, and N. viridula tolerance. This genotype can be used to improve seed biochemical content and plant tolerance against N. viridula.